MALAYSIAN LICHENS âI I * - GROENHART, P. (Research Center for Biology, 1950)
The Umbilicariaceae are a family of Lichens occurring almost exclusively in temperate regions and moreover frequently growing on rocks. Nevertheless this family is represented in the tropics; it has been reportedfrom tropical America and Africa. As far as data are available they occur on rocks in the upper regions of high mountain-ranges, viz. of the Andes of Bolivia and Peru and of Pico dOrizaba in Mexico from 10,000 feet upwards. For Africa the data are in accordance: Mount Deschen in Abyssinia (14,200 feet) and Mount Kilimanjaro in Kenya (12,000 feet). For the tropics of Asia an early record exists of the appearance of a species of Umbilicaria; until today, however, this indication has not yet been confirmed and as far as I could gather, it has remained the only one. In Zollingers